Optical and resonance raman spectroscopy of the heme groups of the quinol- oxidizing cytochrome aa3 of bacillus subtilis - Lauraeus, Marko; Wikström, Mårten; Varotsis, Constantinos (My University, 1992)
The cytochrome aa3-type terminal quinol oxidase of Bacillus subtilis catalyzes the four-electron reduction of dioxygen to water. It resembles the aa3-type cytochrome-c oxidase in using heme A as its active-site chromophores but lacks the Cu(A) center and the cytochrome-c oxidizing activity of the mitochondrial enzyme. We have used optical and resonance Raman spectroscopies to study the B. subtilis oxidase in detail. The α-band absorption maximum of the reduced minus oxidized enzyme is shifted by 5-7 nm to the blue relative to most other aa3-type oxidases, and accordingly, we designate the Bacillus enzyme as cytochrome aa3-600. The shifted optical spectrum cannot be ascribed to an alteration in the strength of the hydrogen bond between the formyl group of the low-spin heme and its environment, as the Raman line assigned to this mode in aa3-600 has the same frequency and degree of resonance enhancement as the low-spin heme a formyl mode in most other aa3-type oxidases. Raman modes arise at 194 and 214 cm-1 in aa3- 600, whereas a single band at about 214 cm-1 is assigned to the iron- histidine stretch for the other aa3-type oxidases. Possible explanations for the occurrence of these two modes are discussed. Comparison of formyl and vinyl modes and heme skeletal vibrational modes in different oxidation states of aa3-600 and of beef heart cytochrome-c oxidase shows a strong similarity, which suggests conservation of essential features of the heme environments in these oxidases
Keywords: Cytochrome oxidase; Raman spectroscopy; Heme; Bacillus subtilis; Chromatophores; Enzymes--Structure; Hydrogen bonding